THE LINK BETWEEN AUTISM SPECTRUM DISORDER AND GASTROINTESTINAL MICROBIOTA - Zafar, Umema; Habib, Syed Hamid (Journal of Ayub Medical College Abbottabad, 2021)
Background: In recent times multiple attempts have been made to search for the link between Autism Spectrum Disorder (ASD) and gut microbiota. This link is not a myth as the microbiota composition and in turn its bi-products effect not only the Gut-Brain axis but also the hypothalamic-pituitary-adrenal (HPA) axis and the immune response. Aim of the study was to find the relation between the Gut Microbiota and the pathophysiology and in turn manifestations of ASD. Methods: Eight original articles were identified by a systematic search of the MEDLINE. database. Those articles were included in the review with clear mention of ASD and microbiota in titles and abstracts. Results: In the majority of studies, Bacteroidetes/ Firmicutes ratio was deranged only one reported it to be normal. Bacteria such as Actinomyces and Proteobacteria were increased and Bacteroides, Bifidobacterium, Lactobacillus, and Prevotella were decreased. The commonest method of sequencing observed was 16S rRNA. Conclusion: The microbiota composition of the gut does affect the manifestations of autism spectrum disorder. The derangement of the gut commensals may lead to mood disorders, depression, and other symptoms in autistic kids.